PENGARUH STRATEGI JOYFUL LEARNING MELALUI SNOWBALL THROWING TERHADAP HASIL BELAJAR SISWA PADA MATERI LARUTAN PENYANGGA - Nabila Fauziah; Nanda Saridewi; Aini Nadhokhotani Herpi (Sindoro: Cendikia Pendidikan, 2024)
Buffer solution is one of the chemical materials that is complex and uses a lot of numerical calculations. Low student learning outcomes in learning are caused by many factors. One of them is the failure of the teacher in creating fun learning for students, teachers must be able to create a learning atmosphere that can encourage students to actively learn. Therefore, it is necessary to apply joyful learning strategies through snowball throwing to improve learning outcomes. The purpose of this study was to determine the effect of joyful learning strategies through snowball throwing on student learning outcomes on buffer solution material. The research method used was quasi experiment. The research design used was nonequivalent control group design. The samples in this study were XI MIPA 2 class totaling 35 students and XI MIPA 3 class totaling 35 students. The research instrument used was a multiple choice test question to see student learning outcomes. Data were analyzed using SPSS. The results of the Mann-Whitney hypothesis test showed a significance value of 0.000 < the significant level of 0.05 which states that Ha is accepted so it can be concluded that the use of Joyful Learning strategies through Snowball Throwing has an effect on student learning outcomes on buffer solution material.